The wealthtech book : the investment technology handbook for money managers, entrepreneurs and change-makers - Chishti, Susanne, 1971-; Barberis, Janos, 1971- (Hoboken : Wiley, 2018)
'Get a handle on disruption, innovation and opportunity in investment technology The digital evolution is enabling the creation of sophisticated software solutions that make money management more accessible, affordable and eponymous. Full automation is attractive to investors at an early stage of wealth accumulation, but hybrid models are of interest to investors who control larger amounts of wealth, particularly those who have enough wealth to be able to efficiently diversify their holdings. Investors can now outperform their benchmarks more easily using the latest tech tools. The WEALTHTECH Book is the only comprehensive guide of its kind to the disruption, innovation and opportunity in technology in the investment management sector. It is an invaluable source of information for entrepreneurs, innovators, investors, insurers, analysts and consultants working in or interested in investing in this space. Explains how the wealth management sector is being affected by competition from low-cost robo-advisors Explores technology and start-up company disruption and how to delight customers while managing their assets Explains how to achieve better returns using the latest fintech innovation Includes inspirational success stories and new business models Details overall market dynamics The WealthTech Book is essential reading for investment and fund managers, asset allocators, family offices, hedge, venture capital and private equity funds and entrepreneurs and start-ups'--
'The WEALTHTECH Book aggregates industry expertise in a single volume. The reader will learn about key developments in the industry and obtain insights of cutting edge practitioners whether entrepreneurs, investors, or advisors in the analytics, data analysis, data mining and actuarial space'--
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Investment analysis -- Handbooks, manuals, etc; Electronic books